Hubungan kemampuan Literasi Sains dengan Keterampilan Berpikir Kritis IPA Siswa Kelas 4 Sekolah Dasar - Risahadi, Putri Nabila; Akbar, Budhi (Publikasi Pendidikan, 2024)
This research aims to examine the connection between fourth graders' scientific literacy and critical thinking abilities in the 2023–2024 school year at SDN Kalibaru 05. Since the study sample included all fourth graders at SDN Kalibaru 05, a saturated sample was the sampling strategy employed. Objective, multiple-choice exams measuring scientific literacy (15 questions) and critical thinking (16 items) were used to gather data. With a dependability of 0.626, the whole instrument was valid. Due to the non-normal distribution of the data, non-parametric Spearman Rank correlation analysis was used for hypothesis testing. This research found a favorable and statistically significant correlation between students' scientific literacy and their ability to think critically. Children who are well-versed in the scientific method are therefore more likely to be capable thinkers. Science literacy and pupils' ability to think critically are two areas that teachers are strongly urged to work on. It is suggested that more studies be conducted to investigate the variables that influence scientific literacy and to evaluate the efficacy of various methods, techniques, and instructional media in this regard.. Keywords: Correlatiom, Science Literacy, Critical Thingking Skills, Science, Elementery School.